2015
DOI: 10.1051/0004-6361/201323018
|View full text |Cite
|
Sign up to set email alerts
|

White dwarf masses in cataclysmic variables

Abstract: Context. The white dwarf (WD) mass distribution of cataclysmic variables (CVs) has recently been found to dramatically disagree with the predictions of the standard CV formation model. The high mean WD mass among CVs is not imprinted in the currently observed sample of CV progenitors and cannot be attributed to selection effects. Two possibilities have been put forward to solve this issue: either the WD grows in mass during CV evolution, or in a significant fraction of cases, CV formation is preceded by a (sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 74 publications
2
50
0
1
Order By: Relevance
“…This is because low-mass WDs are found in large numbers in samples of detached post common envelope binaries (Rebassa-Mansergas et al 2011) and the observed WD mass distribution of these objects is in good agreement with the model predictions (Toonen & Nelemans 2013;Zorotovic et al 2014;Camacho et al 2014). Finally, in Wijnen, Zorotovic & Schreiber (2015) we have shown recently that the two scenarios suggested by ZSG11, i.e. mass growth in CVs or a preceding phase of thermal time scale mass transfer for many CVs cannot solve the WD mass problem in CVs either.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…This is because low-mass WDs are found in large numbers in samples of detached post common envelope binaries (Rebassa-Mansergas et al 2011) and the observed WD mass distribution of these objects is in good agreement with the model predictions (Toonen & Nelemans 2013;Zorotovic et al 2014;Camacho et al 2014). Finally, in Wijnen, Zorotovic & Schreiber (2015) we have shown recently that the two scenarios suggested by ZSG11, i.e. mass growth in CVs or a preceding phase of thermal time scale mass transfer for many CVs cannot solve the WD mass problem in CVs either.…”
Section: Introductionsupporting
confidence: 68%
“…The sample of generated MS binary stars is then evolved until the end of the common envelope (CE) phase using the binary-star evolution (BSE) code from Hurley, Tout & Pols (2002) assuming a CE efficiency of α = 0.25 (Zorotovic et al 2010). The generated population of zero age post-CE binaries is subsequently evolved to obtain the current population of CVs following the approach used in Wijnen, Zorotovic & Schreiber (2015). We simply assume the Mass-Radius relation for CV secondary stars and systemic angular momentum loss prescriptions as derived from observational constraints by Knigge, Baraffe & Patterson (2011).…”
Section: General Model Assumptionsmentioning
confidence: 99%
“…Hailey et al (2016) argue that the excess B-star population needed to explain high WD masses is within the large uncertainty of the expected population in the GC region. On the other hand, the average mass of the WD in the nonmagnetic CVs or isolated magnetic WDs are about 0.8M e (Ferrario et al 2015;Wijnen et al 2015). In addition, there is no clear evidence for high mass progenitors for the WDs in CVs (Zorotovic et al 2011).…”
Section: ) (A-mentioning
confidence: 96%
“…evolution [8]. WDs in the short-period CVs are also hotter (10000-20000 K, [9]) than expected for their age.…”
Section: Geometry Of Short Orbital Period Cvs Primaries and Secondariesmentioning
confidence: 99%